Knowledge, attitudes and practices of healthcare workers towards COVID-19 in three states of Nigeria in 2022 - Alash’le Abimiku; Nifarta Andrew; Elima Jedy-Agba; Rita Okonkwo; Olumide Okunoye; Oyewole Oyedele; Martin Edun; Ugochi Ezenwelu; Asmau Aminu-Alhaji; Aondoakura Kombu; Timothy Attah; Jibreel Jumare; et al. (BMJ Public Health)
Background Knowledge, attitude and practices (KAP) towards COVID-19 can directly impact healthcare workers’ (HCWs) services and efforts to contain the spread of the disease. This study assessed KAP towards COVID-19 among HCWs (laboratorians, doctors, nurses and pharmacists) in Nigeria from August to December 2022.Method A facility-based cross-sectional study was conducted on 1341 HCWs (laboratorians, doctors, nurses and pharmacists) in 7 healthcare facilities across 3 states in Nigeria. HCWs were selected using a stratified random sampling technique. A structured questionnaire including sociodemographic and health information, and KAP sections was administered to participants. Using Bloom’s cut-off, percentages of correct responses to KAP questions were grouped as either satisfactory (≥80%) or unsatisfactory (<80%). Binary logistic regression was used to determine the association between HCWs’ cadre and satisfactory KAP.Results The proportions of HCW with satisfactory KAP were 64.5%, 51.2% and 5.3%, respectively. Laboratorians had the lowest satisfactory KAP scores (59.4%, 45.9% and 2.0%). There was a weak linear relationship between knowledge and practice (r=0.1, p:0.03), knowledge and attitude (r=0.2, p<0.001), and attitude and practice scores (r=0.20, p<0.001). 6–10 years of practice increased HCWs’ odds of satisfactory knowledge (p=0.049). HCWs’ cadre was not significantly associated with knowledge and practice towards COVID-19 (P>.05). However, nurses compared to laboratorians had higher odds of satisfactory attitude (p:0.033). Socio-demographic factors associated with satisfactory attitude towards COVID-19 were age group, gender, marital status, vaccination status, and satisfactory knowledge (p<.05). Satisfactory attitude and marital status were associated with satisfactory practice (p<.05).Conclusion There are gaps in the practice of COVID-19 prevention among HCWs in Nigeria. Additional exploration is needed to understand the challenges of implementing safety protocols across cadres, particularly among laboratorians, to better handle future health emergencies. This study highlights the implementation strategies that include education and training, provision of personal protective equipment and clear guidelines for implementation of infection prevention and control practices.